2008
DOI: 10.1029/2008gl036372
|View full text |Cite
|
Sign up to set email alerts
|

Makassar Strait throughflow, 2004 to 2006

Abstract: The transfer of Pacific water into the Indian Ocean through the Indonesian seas affects the heat and freshwater budgets of both oceans. The observed transport in the Makassar Strait, the primary Indonesian throughflow pathway, from January 2004 through November 2006 is 11.6 ± 3.3 Sv (Sv = 106 m3/s). This transport is 27% larger than observed during 1997 when a strong El Niño suppressed the flow. The 2004‐06 Makassar transport displays clear seasonal behavior, with associated heat and freshwater variability, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
156
4
11

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(195 citation statements)
references
References 16 publications
(24 reference statements)
19
156
4
11
Order By: Relevance
“…1), which was slightly higher than that estimated from the sum of previous direct measurements at different times. During the INSTANT period, the total transport measured through the main entrance channel, the Makassar Strait, was 11.6Sv (Gordon et al 2008).…”
Section: The Itf Transport and Its Interannual And Decadal Variationsmentioning
confidence: 99%
“…1), which was slightly higher than that estimated from the sum of previous direct measurements at different times. During the INSTANT period, the total transport measured through the main entrance channel, the Makassar Strait, was 11.6Sv (Gordon et al 2008).…”
Section: The Itf Transport and Its Interannual And Decadal Variationsmentioning
confidence: 99%
“…Because 2004-2006 are considered normal years [38], there is no evident large interannual variability in the observed volume transports. However, Gordon et al [37] reported increasing transport during those three years in the Makassar Strait.…”
Section: Volume Transportmentioning
confidence: 99%
“…Observations of different passages or straits have been documented in separate papers, such as Gordon et al [38] for the Makassar Strait, Van Aken et al [39] for the Lifamatola Passage and Sprintall et al [4] for the three outflow passages. The INSTANT dataset provides an opportunity to resolve intraseasonal to interannual variability in the ITF, in the vertical structure of the transport and the volume budget of the Indonesian Seas.…”
Section: Instant Datasetmentioning
confidence: 99%
See 1 more Smart Citation
“…2d). This semiannual variability may also be enhanced by remote forcing of the pycnocline/ thermocline associated with the Wyrtki Jets in the equatorial Indian Ocean or with remotely generated signals from the Pacific Ocean (e.g., Wijffels and Meyers 2004;Qu et al 2008;Gordon et al 2008). Additional work is needed, e.g., model sensitivity experiments, to test/separate the role of remotely forced waves on MLT in this region.…”
Section: The Seasonal Mlt Budgetmentioning
confidence: 99%